Meta-Analysis of the Effect of Overexpression of MYB Transcription Factors on the Regulatory Mechanisms of Anthocyanin Biosynthesis - Liu, Weichao; Zheng, Tangchun; Yang, Yujie; Li, Ping; Qiu, Like; Li, Lulu; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2021)
MYBs (v-myb avian myeloblastosis viral oncogene homologs) are important transcriptional regulators that play critical roles in the regulation of anthocyanin biosynthesis. The overexpression of MYB genes has been reported in different plant species. However, the inconsistent strategies to assess transgenic plants have made it difficult to explain the complex mechanisms of regulation of anthocyanin biosynthesis by MYBs. We report here a meta-analysis of 608 studies from 206 publications assessing the effects of MYB overexpression on anthocyanins and evaluate the experimental variables that have an influence on transgenic plant performance. We found that MYB expression enhanced the magnitude of 20 out of 26 examined plant parameters by at least of 21% and reduced the magnitude of 1 indicator by at least 37%. We explored the variety of moderating variables causing these variations. A deeper colour induced by MYBs caused higher plant attributes as compared to normal colour changes. MYB genes from dicots stimulated the accumulation of anthocyanins, flavonols and impacted the expressions of PAL, CHS, CHI, FLS, F3'5'H, ANS, UFGT, and ANR as compared to monocots. Heterologous expression and homologous expression showed a great difference in anthocyanin biosynthesis. Transient gene transformation had a significant effect on the expression of flavonoid biosynthetic genes, and stable transformation had a significant effect on flavonoid accumulation. Stress could result in a significantly increased accumulation of flavonoids, especially anthocyanin, flavonol, and proanthocyanidin. Our study, thus, provides new insights into the function of MYBs in the regulatory mechanisms of flavonoid biosynthesis and the use of genetic engineering for improving anthocyanins contents.